Surveillance of Surgical Site Infection in the post-discharge follow-up (Research, Society and Development, 2023)
Healthcare-Associated Infections are a major public health problem faced by hospitals around the world. One of the most incidents is the Surgical Site Infection, a complication of the surgery that culminates in damage to the patient and increases treatment costs. Post-discharge surveillance is an essential tool in the early detection of possible complications of the surgery, in a way that provides effective and rapid intervention and greater patient safety. Objective: To analyze in the scientific literature the instruments used to carry out post-discharge surveillance, in a safe and effective way, in hospitals in Brazil and around the world. Methodology: This is an integrative review, following the guidelines outlined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, the time series was from 2017 to 2022. 583 articles were identified, which, after analysis based on the eligibility criteria, reduced to 19. It was noticed that, in a large part of the world, post-discharge surveillance has achieved excellent results. Phone search was well evidenced in studies carried out in Brazil, Africa, Asia, New Zealand. A study carried out in Ghana showed a reduction in hospital costs of up to 25%. Countries such as Canada, Australia, England and Italy have invested in applications and software. Conclusion: The post-discharge surveillance method has shown beneficial results in the early identification of infections and reduces complications.